Mining foreign language teaching manuals for the history of pragmatics - McLelland, Nicola (John Benjamins, 2018)
Foreign language learning manuals can be valuable sources for the history of pragmatics and historical pragmatics. They may contain explicit guidance on pragmatics not found in native-speaker grammars: for example, accounts of German forms of address in seventeenth and eighteenth-century English-German manuals provide evidence of changing views on the appropriateness of ihr and Sie earlier than does the “native” grammatical tradition. The bilingual model dialogues typical of such manuals may also implicitly model appropriate linguistic behaviour, demonstrated here by examining the communicative genre of bargaining in a series of three related English-Dutch language manuals of the seventeenth and eighteenth centuries. Furthermore, the dialogues may provide metalinguistic comment on linguistic behaviour, for example criticizing the culture of excessive negative politeness. Such sources can enrich our knowledge of language use and attitudes to language use in the area of politeness, complementing the evidence to be gleaned from mainstream native grammars, civility manuals, merchants’ guides, and the like.